The understandings of revelation in Christianity: Patterns of development and an Islamic perspective - Mohd Daud, Noor Amali (2013)
The primary aim of this paper is to explore in details the theological discourse on revelation, the meanings and its understandings in selected Christian writings. The study is based on the premise that there are changing interpretations on and various expressions of the doctrine of revelation in Christian writings. In this regards, the Biblical notion of revelation will be highlighted to gain insight on traditional understandings of the issue. The discussion will be deliberated further by investigating the development of the concept in modern as well as contemporary Christian writings upon its conversation with specific cultural and philosophical contexts. Patterns of understandings of revelation will be highlighted and thoroughly discussed. Islamic appraisal on this central issue will be focused on to compare between the concept of revelation in Christianity and wahy in Islam.